2016
DOI: 10.1016/j.antiviral.2016.10.006
|View full text |Cite
|
Sign up to set email alerts
|

HDV RNA replication is associated with HBV repression and interferon-stimulated genes induction in super-infected hepatocytes

Abstract: Hepatitis D virus (HDV) super-infection of Hepatitis B virus (HBV)-infected patients is the most aggressive form of viral hepatitis. HDV infection is not susceptible to direct anti-HBV drugs, and only suboptimal antiviral responses are obtained with interferon (IFN)-alpha-based therapy. To get insights on HDV replication and interplay with HBV in physiologically relevant hepatocytes, differentiated HepaRG (dHepaRG) cells, previously infected or not with HBV, were infected with HDV, and viral markers were exten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
96
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 81 publications
(107 citation statements)
references
References 52 publications
11
96
0
Order By: Relevance
“…111 Little data have been published on the virological characteristics of HDV-infected immigrants. As expected from the well-known interaction between the two viruses, 126 Rivas et al 124 HBsAg serum levels were lower in HDV-coinfected than in HBV-…”
Section: Epidemiologymentioning
confidence: 67%
See 2 more Smart Citations
“…111 Little data have been published on the virological characteristics of HDV-infected immigrants. As expected from the well-known interaction between the two viruses, 126 Rivas et al 124 HBsAg serum levels were lower in HDV-coinfected than in HBV-…”
Section: Epidemiologymentioning
confidence: 67%
“…Little data have been published on the virological characteristics of HDV‐infected immigrants. As expected from the well‐known interaction between the two viruses, Rivas et al showed that the median serum HBV DNA was significantly lower in HDV‐positive than ‐negative patients. Similarly, Heidrich et al demonstrated that both the HBV‐DNA positivity rate (29% vs 53%, P < .001) and HBsAg serum levels were lower in HDV‐coinfected than in HBV‐monoinfected.…”
Section: Hdv Infection In Immigrant Populationsmentioning
confidence: 71%
See 1 more Smart Citation
“…In contrast to HDV [47,48], HBV infections seem to be associated with a lack of induction or even a decreased expression of ISGs or other pro-inflammatory genes, thus pointing toward mechanisms of active inhibition. The first demonstration that HBV could inhibit PRR signaling pathways came from a study, which showed that both HBeAg and HBsAg could antagonize the antiviral action of PRR agonists in murine parenchymal and non-parenchymal cells [49].…”
Section: Interplay Between Hbv and Innate Immunity: Basic Insightsmentioning
confidence: 99%
“…It seems appropriate to indicate that if the HBV-driven strategies to inhibit immune responses are genuine, they are only adapted to what HBV itself would be able to trigger as a weak inducer of innate responses; indeed, it seems that HBV-mediated inhibitory phenotypes are not very potent and are likely not capable of fully counteracting a more aggressive induction of innate responses, like that mediated, for instance, by HDV [48]. …”
Section: Interplay Between Hbv and Innate Immunity: Basic Insightsmentioning
confidence: 99%